Analisa Pembelajaran Keterampilan Berbicara Santri Kelas VII SMPIT Al Bashiroh Boarding School Turen Malang - Damayanti, Aldina; Anwar, Najih (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This study aims to determine the learning process of maharah kalam students as well as to determine the planning, implementation and evaluation of learning maharah kalam as well as analyzing the supporting and inhibiting factors in learning maharah kalam for 7th grade students at SMPIT Al Bashiroh Boarding School Turen Malang. In this study, the method used to support the smoothness of the researcher is to use descriptive qualitative methods. Obtaining research data to be analyzed in the form of observation, documentation and interviews. The results of the study indicate that the Maharah Kalam lesson plan is in the form of an annual program, syllabus and lesson plan. The implementation of maharah kalam learning activities went quite well, while the evaluation carried out in the form of reporting and follow-up, but the exam for maharah kalam was only held in class IX. While the results of research regarding the supporting factors are the enthusiasm of students to learn and get used to maharah kalam and the existence of a dictionary in the library to support learning maharah kalam students, for the inhibiting factors are aspects of difficulty in mastering vocabulary in Arabic, individual abilities, learning methods and aspects infrastructure.